STRUCTURE AND FLORISTIC COMPOSITION IN A DENSE OMBROPHILOUS FOREST AREA UNDER FOREST MANAGEMENT - Ramos, Yasmim Andrade; Aguiar, Bruno Aurélio Campos; Silva, Marcos Vinicius Cardoso; Matos, Renata Elaine Siqueira; Coelho, Maria Cristina Bueno; Giongo, Marcos (Floresta, 2019)
This study shows the phytosociology and floristics of a Dense Ombrophilous Forest fragment under forest management in Portel city, Pará State. Six conglomerates were sampled, divided into secondary and tertiary plots totaling 120 sample units of 0.4 hectares each, in which all trees with diameter at breast height (130 cm above ground; DBH) above 10 cm were measured. These individuals were botanically identified, and evenness and floristic similarity were calculated. There were 3,586 individuals distributed in 42 families, 121 genera, and 174 species. Families Fabaceae, Lecythidaceae, and Sapotaceae were the ones that obtained the highest IVI and the highest representativity of individuals. Species Eschweilera coriacea (DC.) S.A.Mori, Vouacapoua americana Aubl., and Tetragastris altissima (Aubl.) Swart were the ones with the highest IVI. Among the ten highest results, we highlight Syzygiopsis oppositifolia Ducke and Manilkara dardanoi Ducke, with great potential for timber production. The Shannon diversity index averaged 3.83 between the plots, and the Pielou evenness averaged 0.84, showing that the area presents high floristic diversity and great potential for forest management activities.